Efficiency of Biostimulants for Alleviating Shade Effects on Forage Grass - Lopes, Monyck Jeane dos Santos; Dias-Filho, Moacyr Bernardino; Castro, Thomaz Henrique dos Reis; Gurgel, Ely Simone Cajueiro; Silva, Gisele Barata da (Journal of Agricultural Studies, 2021)
Shade is considered an abiotic stress factor which reduce the primary metabolism and restricts normal growth in forage grass in integrated systems. Biostimulants are beneficial in promoting growth and protecting plants against environmental stresses. This is the first study that links biostimulants and the primary metabolism of plants grown under contrasting light intensities. We investigated how the use of biostimulants modifies the primary metabolism, reducing the deleterious effects of shading in the development of tropical forage grass Brachiaria brizantha cv. BRS Piatã. The association of Pseudomonas fluorescens and Burkholderia pyrrocinia, inoculated by soil drench, were used as biostimulants. We measured leaf anatomy, plant growth, and biochemical parameters. The use of biostimulants increased the shade tolerance on B. brizantha by modifying leaf structure, increasing the chlorophyll content, and inducing the production of osmoregulants, such as carbohydrates and proteins. In turn, increasing the accumulation of primary metabolites, promoted root development, plant height, and leaf area, resulting in more vigorous plants with greater biomass production. These results suggested that forage grass can be protected from inhibitory effects of the shade stress by the biostimulants, and this would improve its survival and growth in integrated crop-livestock-forestry systems.